Diffraction of EM-wave by a slit of finite width with Dirichlet conditions in cold plasma. (24th September 2021) - Javaid, Ayesha; Ayub, Muhammad; Hussain, Sajjad; Haider, Sabih; Abbas Khan, Ghulam
Abstract: In the present communication, we have carefully analyzed the interaction of incident wave field on a slit of finite width under the imposition of Dirichlet boundary conditions in the presence of cold plasma. The boundary value problem is established after implementing the Fourier transform on Helmholtz equation. The Wiener-Hopf analysis is utilized to sort out the problem proposed for this model. The separated field is evaluated and its numerical results are presented, at the end of the analysis, to further study the effects of various physical parameters in the presence of cold plasma.